A Nineteenth-Century Catholic Translation of the Qur'an into Italian by Vincenzo Calza, Pontifical Consul General of Algiers. Issue 3 (September 2022) - Stella, Federico
Abstract : This article addresses the first complete Italian translation of the Qur'an, Il Corano, versione italiana con commento e una notizia biografica di Macometto, which was authored by Vincenzo Calza, the first Pontifical General Consul in Algiers, and published in 1847. After contextualising the author and his work with a brief biographical introduction, the article identifies the origins of Calza's interest in his study of Islam and the Qur'anic text, as well as his objective in engaging with these subjects. It then turns to his translation, Il Corano, and traces back the sources used by Calza in his introduction to and translation of the Qur'anic text, and the critical apparatus he employed. Calza himself claimed that his Qur'an translation was based on the original Arabic text with the help of Kazimisrki's translation, Le Koran, and Carlo Alfonso Nallino has stated that Calza's translation relied heavily on Kazimirski's first flawed edition of Le Koran (1840), which was, in turn, based on Claude-Étienne Savary's 1783 translation. Through textual analysis and comparison, in this article we find that, in fact, Calza relied entirely on the second, 1841, edition of Kazimirski's Le Koran, in which Kazimirski corrected many errors that were present in the first edition. Calza also selectively adopted elements from Kazimirski's introduction to his translation, and, through this, much of his methodological apparatus.